2021
DOI: 10.21833/ijaas.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

How does emotional intelligence improve employee satisfaction and performance with mediating effect of employee engagement? Perspective from Saudi Arabian private companies

Abstract: The main focus of this study is to examine how Emotional Intelligence (EI) improves Employee Job Satisfaction and Performance (EJSP) with mediating effect of Employee Engagement (EE) in private sector organizations of the Kingdom of Saudi Arabia (KSA). The nature of the research study is quantitative, and a correlational design has been adopted for the study. Primary data was collected from a sample of 537 employees of private organizations in major cities of KSA. SPSS and Smart PLS were used to run different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Individuals with high levels of EI could code and decode their personal and other people’s emotions and manage their emotional behaviors by adapting to their work’s emotional demands. Alferaih (2021) revealed that EI positively impacted the performance and JS level of employees where engagement mediated the relationship between EI and JS. The findings of Bano et al (2021) revealed that all dimensions of EI showed significant positive correlation with JS.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Individuals with high levels of EI could code and decode their personal and other people’s emotions and manage their emotional behaviors by adapting to their work’s emotional demands. Alferaih (2021) revealed that EI positively impacted the performance and JS level of employees where engagement mediated the relationship between EI and JS. The findings of Bano et al (2021) revealed that all dimensions of EI showed significant positive correlation with JS.…”
Section: Literature Reviewmentioning
confidence: 94%
“…PLS (Arshad et al, 2023;Alferaih, 2021) AMOS (Anwar et al, 2017;Clarke & Mahadi, 2017;Rahmawaty et al, 2021) SPSS (Anwar et al, 2017;Clarke & Mahadi, 2017;Sabie et al, 2020)…”
Section: Software Used In the Studyunclassified
“…Based on empirical studies, it has been shown that emotional intelligence exerts a noteworthy influence on an employee's performance (Alferaih, 2021). The presence of heightened emotional intelligence significantly influenced the amount of organizational resilience among employees (Dhoopar et al, 2022).…”
Section: Outcome Of the Studymentioning
confidence: 99%
“…The study aims to offer valuable insights into the methodological advancements within the domain of emotional intelligence (EI) as a learnable skill that can be cultivated. Enhancing employees' emotional intelligence (EI) is crucial for achieving a notable level of performance and pleasure within the working environment (Alferaih, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%